NF-κB/p65 Competes With Peroxisome Proliferator-Activated Receptor Gamma for Transient Receptor Potential Channel 6 in Hypoxia-Induced Human Pulmonary Arterial Smooth Muscle Cells - Wang, Yan; Li, Naijian; Wang, Yingfeng; Zheng, Guobing; An, Jing; Liu, Chang; Wang, Yajie; Liu, Qicai (Frontiers in Cell and Developmental Biology, 2021)
Objective: PPARγ had an anti-proliferation effect in pulmonary arterial smooth muscle cells (PASMCs) by transient receptor potential channel (TRPC) and has a protective effect against pulmonary artery hypertension (PAH), while nuclear factor-kappaB (NF-κB) has pro-proliferation and pro-inflammation effects and contributes to PAH. However, association between them in PAH pathology is still unclear. This study aimed to investigate it and themechanismsofTRPC1/6 signaling-mediated PAH. Methods: hPASMCs were transfected with p65 overexpressing (pcDNA-p65) and interfering plasmids (shp65) and incubated in normal and hypoxia conditions (4% O2 and 72 h). The influence of hypoxia and p65 expression on cell proliferation, invasion, apoptosis, [Ca2+]i, PPARγ and TRPC1/6 expression were determined using using CCK-8, transwell, Annexin V/PI, Fura-2/AM, and western blot, respectively. The binding of p65 or PPARγ proteins to TRPC6 promoter was validated using the dual-luciferase report assay, CHIP-PCR, and EMSA assay. Results: Hypoxia inhibited hPASMC apoptosis, promoted cell proliferation and invasion. It also increased [Ca2+]i and enhanced the expression of TRPC1/6, p65, and Bcl-2 proteins. Besides, pcDNA-p65 had similar and supportive effects on hypoxia treatment by enhancingTRPC1/6expression, [Ca2+]i, hPASMC proliferation and invasion. The dual-luciferase report and ChIP-PCR assays determined there were three p65 binding sites and two PPARγ binding sites on the promoter region of TRPC6. In addition, hypoxia treatment and shPPARγ promotedthe binding of p65 to TRPC6 promoter, while shp65 promoted the binding of PPARγ to TRPC6 promoter. Conclusions: The competitive binding of NF-κBp65andPPARγtoTRPC6 promoter had acontrary effect on PAH.